The potential of green roof strategies for reducing CO2 emissions and energy use in Moroccan office buildings - Abdessamad Idouanaou; Mustapha Malha; Abdellah Bah; Saïd Kardellass (Green Technologies and Sustainability)
Green roofs are increasingly recognized as a sustainable strategy for mitigating energy consumption and reducing CO2 emissions in buildings. This study evaluates the potential of green roofs in Moroccan office buildings across six climatic zones, focusing on three critical design parameters: Leaf Area Index (LAI), plant height, and minimum stomatal resistance (MSR). Through simulations conducted using EnergyPlus, the results reveal significant energy-saving potential, particularly in hotter zones, where cooling demand is dominant. Taller plants and higher LAI values enhance shading and evapotranspiration, reducing cooling energy use by up to 4.75%, but they also increase heating energy requirements during cooler months by up to 20.23%. The findings underscore the need for region-specific optimization, including strategies like seasonal plant height adjustment and LAI selection, to balance cooling benefits and heating trade-offs. By providing insights into the thermal and environmental performance of green roofs, this research contributes to the development of practical design guidelines for integrating sustainable building practices into Morocco’s growing urban landscape.